Annals of Occupational and Environmental Medicine - Ko, Sang Baek; Kim, Ji-Hyun
Annals of Occupational and Environmental Medicine (AOEM) is an open access journal that considers original contributions relevant to occupational and environmental medicine and related fields, in the form of original articles, review articles, short letters and case reports. AOEM is aimed at clinicians and researchers working in the wide-ranging discipline of occupational and environmental medicine. Topic areas focus on, but are not limited to, interactions between work and health, covering occupational and environmental epidemiology, toxicology, hygiene, diagnosis and treatment of diseases, management, organization and policy. As the official journal of the Korean Society of Occupational and Environmental Medicine (KSOEM), members and authors based in the Republic of Korea are entitled to a discounted article-processing charge when they publish in AOEM.